D1A, D1B, and D1C dopamine receptors from Xenopus laevis. - Sugamori, K S (1994)
Three distinct genes encoding members of the D1 dopamine receptor family were isolated from Xenopus laevis. Based on the deduced amino acid sequence, two of the receptors (Xen D1A and Xen D1B) appear to be homologues of mammalian D1/D1A and D5/D1B receptors. The third receptor, termed Xen D1C, displays equal overall amino acid and nucleotide sequence identity (approximately 55%) with mammalian D1A and D1B/D5 receptors. In agreement with their structural similarities, Xen D1A and D1B receptors, when expressed in COS-7 cells, displayed pharmacological profiles that paralleled those of their mammalian counterparts, with dopamine and 2-amino-6,7-dihydroxytetralin exhibiting 10-fold higher affinity for D1B than for D1A. The Xen D1C receptor displayed an overall rank order of potency and pharmacological profile clearly indicative of a D1-like receptor, with individual affinities for most agonists higher than those for either Xen or mammalian D1/D1A and D5/D1B receptors, whereas antagonist Ki values were intermediate to those for the D1/D1A and D5/D1B receptors. All three receptors stimulated adenylate cyclase activity in response to dopamine or SKF-82526. Xen D1A, D1B, and D1C receptor mRNAs were differentially distributed, with all three receptors expressed in brain and only D1B and D1C receptors expressed in kidney. The existence of a receptor which lacks appreciable overall sequence similarity to, but displays pharmacological homology with, mammalian D1-like receptors lends strong support to the contention that additional mammalian D1-like receptor gene products may exist to allow for the expression of the full spectrum of D1-like dopamine receptor-mediated events.